Evaluation on green concept of high-rise building design and its architectural feasibility - Johanes Krisdianto; FX Teddy Badai Samodra; Mudji Irmawan (IPTEK Journal of Proceedings Series, 2017)
Recently, the feasibility study on occupancy, building design and its operation are critical issues in building certification. This study evaluates green concept of a high-rise building, Grand Darmo Suite Hotel Surabaya-an awarded on green building as case study, to the architectural feasibility. The modeling using Ecotect Analysis and CFD Fluent program combined with field observation were also conducted to evaluate the building performance. Based on building simulation and the walkthrough survey and audit, the results show that the building has architectural aspect and advantage, it remains in consistent way between the initial planning and the development. In general, the green concept is implemented in organization of space and its use where they are in accordance with the functions and appropriate to building permit. Furthermore, the condition and quality of the finishing material do not interfere the comfort of occupancy.